Mission valence of civil servants: development and validation of a three-dimensional scale - Liu, Xi; Zhao, Mengchu; Zheng, Weibo (Frontiers in Psychology, 2026)
BackgroundIn the context of public service reform and sustained governance optimization, mission valence is a pivotal driver of public service behavior, yet existing measurements are predominantly unidimensional. These simplified tools often fail to capture the complex psychological process of civil servants within the organizational settings of the public sector. A multidimensional instrument is therefore essential to accurately reflect this construct.Methods and resultsThis study develops and validates a multidimensional mission valence scale for civil servants using a mixed-methods design. Study 1 (N = 21) conducted grounded theory interviews to derive content domains and initial items inductively. Study 2 firstly applied item analysis and exploratory factor analysis (N = 205), yielding a 12-item scale with three dimensions: Value Attribute Assessment, Affective Role Identity, and Behavioral Transformation Intention. Subsequently, we conducted confirmatory factor analysis (N = 216) to verify the structure and assess reliability and validity. Across samples, the model fit was good, internal consistency and composite reliability were strong, and convergent and discriminant validity were satisfactory. Study 3 (N = 456) supported criterion-related validity, indicating that servant leadership exhibits a significant positive association with mission valence, mediated by public service motivation.ConclusionThe findings developed a psychometrically sound instrument that reconstructs civil servants’ mission valence as a multidimensional process. This validated scale provides a precise tool for examining the mechanisms underlying civil servants’ mission valence in public sector organizational behavior.